Criteria for authenticity in historical Jesus research: Some methodological considerations - Buglass, AE (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Different stages of the study of the historical Jesus have developed and refined different criteria by which traditions are sifted to reveal historical nuggets, of which the latest is the criterion of historical plausibility. These criteria are being evaluated in this article. It is argued that no criteria can offer historical certainty, but they do provide help to arrive at a degree of probability. The proper use of the criterion of historical plausibility may lead to a better understanding of the Jesus traditions.